1966
DOI: 10.1063/1.1708325
|View full text |Cite
|
Sign up to set email alerts
|

Some Neutron-Diffraction Investigations at the Nuclear Center of Grenoble

Abstract: In orthorhombic CrRO3 (R=rare earth and Y), Cr spins are ordered in a G mode between TN 282°K for R=La, to 112°K for R=Lu. The rare-earth ordering is coupled to the Cr-spin ordering, with the exception of terbium. In the magnetoelectric compound Fe1.15Ga0.85O3, four sites are available for cations, one of these mainly occupied by Ga. Neutron-diffraction and magnetic-susceptibility measurements give evidence of a ferrimagnetic ordering. Tetragonal FeS shows no evidence for magnetic ordering by neutron diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
1

Year Published

1969
1969
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 7 publications
3
59
1
1
Order By: Relevance
“…A magnetic refinement was performed with G-type spin structure. As shown in Figure 2 [18] and BiCrO 3 (2.55 m B ). [19] Conversely, this fact supports the refined composition of SrCr 3+ O 2 H. With increasing temperature, the magnetic peak decreases gradually and finally vanishes at around T N % 380 K (Figure 3).…”
Section: Angewandte Communications Cations (Versus La 3+mentioning
confidence: 93%
“…A magnetic refinement was performed with G-type spin structure. As shown in Figure 2 [18] and BiCrO 3 (2.55 m B ). [19] Conversely, this fact supports the refined composition of SrCr 3+ O 2 H. With increasing temperature, the magnetic peak decreases gradually and finally vanishes at around T N % 380 K (Figure 3).…”
Section: Angewandte Communications Cations (Versus La 3+mentioning
confidence: 93%
“…On the other hand, neutron diffraction studies have failed to resolve the second magnetic transition as well as the spin configuration of the PrPr exchange interactions at lower temperatures. E. F. Bertaut et al [58] observed spin ordering with a weak ferroelectric component, F x , above 4.2 K without referring to a Pr magnetic ordering. Afterwards, N. Shamir et al [46] identified a weak magnetic structure (C y F x magnetic structure) by neutron scattering studies at 9 K for the PrCrO 3 compound.…”
Section: Discussionmentioning
confidence: 99%
“…The small increasing found in the susceptibility below 10 K are due to presence of a small amount of TbCrO 3 , around 8%, also detected from X-ray diffraction and included in the Rietveld refinement as it can be observed in Fig. 1 [14].…”
Section: Magnetic Propertiesmentioning
confidence: 68%